ANALISIS PROSES QUALITY CONTROL PADA PRODUKSI CYLINDER COMP DI PT.X - Lyoni Elisabet Marpaung (Jurnal Teknovasi : Jurnal Teknik dan Inovasi, 2021)
This research is focused on the Quality Control Cylinder Comp Analysis of motorcycles in maintaining product quality according to consumer needs and desires. The research was conducted at PT.X which is engaged in manufacturing, and distributor of X brand motorbikes. The problems that are in this study include; Incoming Quality Control (IQC), Process Quality Control (IPQC), and Outgoing Quality Assurance (OQA). The purpose of this research is to ensure that all materials or suppliers comply with the specified standards before being used in the production process, assisting the quality control system during the production process to wait and problems that may arise during the production process, and ensure that the products to be sent are free from defects. before reaching the customer. This research uses descriptive qualitative method. The type of data used is primary data. Primary data collection uses interview techniques, so that information can be obtained according to the company. The results of research and data collection show that the quality control in maintaining the quality of the Comp Cylinder starting from Incoming Quality Control (IQC), In Process Quality Control (IPQC), and Outgoing Quality Assurance (OQA) in accordance with the SOP and specifications of PT. X.